2002
DOI: 10.1085/jgp.20028581
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-activated K+ Channels of Mouse β-cells are Controlled by Both Store and Cytoplasmic Ca2+

Abstract: A novel calcium-dependent potassium current (Kslow) that slowly activates in response to a simulated islet burst was identified recently in mouse pancreatic β-cells (Göpel, S.O., T. Kanno, S. Barg, L. Eliasson, J. Galvanovskis, E. Renström, and P. Rorsman. 1999. J. Gen. Physiol. 114:759–769). Kslow activation may help terminate the cyclic bursts of Ca2+-dependent action potentials that drive Ca2+ influx and insulin secretion in β-cells. Here, we report that when [Ca2+]i handling was disrupted by blocking Ca2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 64 publications
(110 reference statements)
8
93
1
1
Order By: Relevance
“…Inhibition of PKC (2 μ M Ro31-8220; Barman et al, 2004 ) combined with a block of SR Ca 2+ -ATPase (0.2 μ M thapsigargin; Goforth et al, 2002 ) caused a mild but consistent increase in current ( Fig. 7, B and G ), suggesting that PKC inhibition of myocyte BK channels ( Barman et al, 2004 ) prevails over channel activation by sarcoplasmic Ca 2+ ( Goforth et al, 2002 ) ( Fig.…”
Section: Pip 2 Regulates Cerebrovascular Tone Via Bk Channelsmentioning
confidence: 89%
See 1 more Smart Citation
“…Inhibition of PKC (2 μ M Ro31-8220; Barman et al, 2004 ) combined with a block of SR Ca 2+ -ATPase (0.2 μ M thapsigargin; Goforth et al, 2002 ) caused a mild but consistent increase in current ( Fig. 7, B and G ), suggesting that PKC inhibition of myocyte BK channels ( Barman et al, 2004 ) prevails over channel activation by sarcoplasmic Ca 2+ ( Goforth et al, 2002 ) ( Fig.…”
Section: Pip 2 Regulates Cerebrovascular Tone Via Bk Channelsmentioning
confidence: 89%
“…7, B and G ), suggesting that PKC inhibition of myocyte BK channels ( Barman et al, 2004 ) prevails over channel activation by sarcoplasmic Ca 2+ ( Goforth et al, 2002 ) ( Fig. 8 ).…”
Section: Pip 2 Regulates Cerebrovascular Tone Via Bk Channelsmentioning
confidence: 90%
“…More recent models of bursting in b-cells include those by Chay (1996), Keizer and Smolen (1989), and Sherman et al (1988). In one recent b-cell model, the Phantom Bursting Model (PBM), bursting is driven by the interaction of more than one slow variable Goforth et al, 2002). In the PBM, the burst period ranges from a few seconds to a few minutes, depending upon the conductance of the various ionic currents.…”
Section: Discussionmentioning
confidence: 99%
“…Several models have been developed for bursting in pancreatic b-cells Chay, 1996;Chay and Keizer, 1983;Goforth et al, 2002;Keizer and Smolen, 1991;Sherman et al, 1988). These models differ primarily in the slow process responsible for driving the bursting.…”
Section: Model For Electrical Burstingmentioning
confidence: 99%
“…Neither tolbutamide nor diazoxide had any effect on V m oscillations in K ATP null islets. The activation of a low-conductance, Ca 2+ -dependent K + current, termed "I Kslow ," has been implicated in the oscillatory activity of wild-type β cells [61,62]. Haspel et al [65] showed that Sur1KO β cells have a similar Ca 2+ -dependent K + current that is inhibited when [Ca 2+ ] c is reduced using D600, an L-type Ca 2+ channel blocker, and stimulated using BayK 8644, a Ca 2+ channel opener.…”
Section: Transgenic Mouse Modelsmentioning
confidence: 99%